CLINICAL CHARACTERISTICS IN THE PATIENTS WITH MASKED UNCONTROLLED NOCTURNAL HYPERTENSION MEASURED BY NIGHTTIME HOME BLOOD PRESSURE MONITORING: THE J-HOP NOCTURNAL BLOOD PRESSURE ST. (April 2021) - Narita, Keisuke; Hoshide, Satoshi; Kario, Kazuomi
Abstract : Objective: Various international guidelines on the management of hypertension recommend nighttime blood pressure (BP) measurements in specific conditions such as sleep apnea, secondary hypertension, etc. However, we physicians sometimes miss nocturnal hypertension in patients with controlled daytime (morning and evening) home BP (HBP), i.e. "masked uncontrolled nocturnal hypertension". Risk factors of masked uncontrolled nocturnal hypertension remain unclear in clinical practice and we thus assessed that using a dataset of the Japan Morning Home-Surge BP (J-HOP) Nocturnal BP study. Design and method: This is a cross-sectional, post-hoc analysis using the dataset of the J-HOP Nocturnal BP study, which recruited patients with risk factors of CVD. Participants underwent consecutive 14-day HBP measurements (morning and evening) and nighttime HBP measurements (a.m. 2, 3, and 4). In the present study, masked uncontrolled nocturnal hypertension was defined as controlled daytime HBP (mean of morning and evening home systolic BP [SBP] < 135 mmHg and diastolic BP [DBP] < 85 mmHg) and uncontrolled nighttime HBP (mean nighttime home SBP > = 120 or DBP > = 70 mmHg). To detect the risk factors of masked uncontrolled nocturnal hypertension, we used traditional host factors, using each type of antihypertensive medications, and markers of target organ damage (urine-albumin creatinine ratio [UACR] and b-type Natriuretic peptide) as covariant in stepwise logistic regression models. Results: Among 1490 participants with controlled daytime HBP levels (age, 62.5 ± 9.7yrs; 49% of male; antihypertensive medication use, 82.2%), male, diabetes, elevated office BP, and log-UACR were significant risk factors for masked uncontrolled nocturnal hypertension in multivariate logistic regression models (OR [95%CI]: male, 1.42 [1.11–1.82]; diabetes, 1.41 [1.09–1.83]; elevated office BP, 1.72 [1.38–2.14]; log-UACR, 1.35 [1.06–1.71]) (Table). Whereas, combination therapy of more than three antihypertensives including diuretics showed a lower odds ratio (0.56 [0.40–0.78]). Figure. No caption available. Conclusions: In the present study, we revealed that male, diabetes, elevated office BP, and highly log-UACR were suggested to be risks for masked uncontrolled nocturnal hypertension. A nighttime HBP monitoring might be recommended for patients who have these risks even if they are controlled daytime HBP levels.